Fremmede konsuler i Norge ca. 1660-1905 - Leira, Halvard; Neumann, Iver B. (Historisk Tidsskrift, 2013)
Foreign Consuls to Norway, c. 1660-1905Consular services predate modern diplomacy by several centuries, yet have received only scant attention from historians of inter-state relations. From the 16th Century and onwards there have been far more consuls than diplomats, they have covered far more cities than the diplomats, and in the hustle and bustle of everyday life they have been far more important than the diplomats in making the less spectacular parts of international society function. In this article we highlight the importance of the consular institution, by detailing both the emergence of the consular institution in the Mediterranean in the years after the crusades and its development into a more modern recognisable form around the North Sea in the 17th Century. Of central concern are the changing roles and practices of consuls, as seen through the activities of the foreign consuls to Norway from around 1660 to the beginning of the 20th Century. The recruitment of consuls, their social position, and the changing relative importance of their roles in politics, diplomacy and local community life are among the various aspects discussed. Besides the consequences of general change in societal organization over time, the historical transformations of the constitutional status of Norway, from possession of the Danish absolute monarch over semi-independent state, in personal union with Sweden, to sovereign nation, offer the advantage of studying the consular institution under different state systems. The essential feature of the consular institution appears to be its great adaptability, not being restricted to one singular function or modus operandi, but simply with the task of representing and assisting foreign states and their citizens as the common denominator across different epochs and institutional settings.